2020
DOI: 10.1021/acssuschemeng.0c03161
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Factors That Affect Food-Waste Storage: Toward Maximizing Lactate Accumulation for Resource Recovery

Abstract: In the U.S., several states have attempted to mitigate greenhouse-gas emissions by banning food wastes from landfills. As a result, U.S.-based companies are now providing decentralized food-waste management systems for supermarkets and restaurants, which include storage as a slurry. It is unclear, however, which storage conditions (factors) would affect the spontaneous microbial activity, resulting in a different fermentation product spectra, and how this would further affect post-treatment. Here, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
(77 reference statements)
1
10
0
Order By: Relevance
“…Such VS destruction values were similar to those previously found during the acidogenesis of FW, which have been reported to range between 26 and 50% (Kim et al, 2009;Moon et al, 2015). On the other hand, it is well established that the pH of the fermentation broth is one of the major influencing factors in the performance of acidogenic systems (Daly et al, 2020;Infantes et al, 2011;Sarkar et al, 2021), and thus it also affected the extent and rate of the evolved biogas (Table 1).…”
Section: Tablesupporting
confidence: 88%
See 1 more Smart Citation
“…Such VS destruction values were similar to those previously found during the acidogenesis of FW, which have been reported to range between 26 and 50% (Kim et al, 2009;Moon et al, 2015). On the other hand, it is well established that the pH of the fermentation broth is one of the major influencing factors in the performance of acidogenic systems (Daly et al, 2020;Infantes et al, 2011;Sarkar et al, 2021), and thus it also affected the extent and rate of the evolved biogas (Table 1).…”
Section: Tablesupporting
confidence: 88%
“…From a bioenergetic viewpoint, lactate is the most energetically favorable acidogenic end-product for methanization (Pipyn and Verstraete, 1981). The use of acidified FW rich in lactate has indeed been found to mediate higher biogas production in comparison with unfermented FW (Daly et al, 2020, Guan et al, 2021. However, the knowledge of the design and operational conditions required to optimize the lactate type-fermentation of FW is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…One of the biotechnology production platforms that is of interest for renewable chemical production is microbial chain elongation. Chain elongation harnesses the potential of certain microbes in anaerobic fermentation biotechnology to generate medium-chain carboxylic acids (MCCAs, C6-C12) through a microbial fermentation pathway with an electron acceptor, such as short-chain carboxylic acids (SCCAs, C2-C5), and an electron donor (e.g., ethanol or lactic acid), which can be obtained through the hydrolysis of organic biomass (Angenent et al, 2016;Xu et al, 2018;Daly et al, 2020) or added to the waste. The pathway of reverse β-oxidation is considered a thermodynamically favorable microbial fermentation pathway to produce MCCAs (Dellomonaco et al, 2011;González-Cabaleiro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because the digesters were buffered periodically and not continually, it is possible that the pH dropped to acidic levels thereby reducing hydrogen production. Another study has shown that H 2 production is influenced by substrate composition with lipid‐rich substrates yielding high H 2 concentrations 45 . Corn stover has negligible lipid content.…”
Section: Resultsmentioning
confidence: 99%
“…Another study has shown that H 2 production is influenced by substrate composition with lipid-rich substrates yielding high H 2 concentrations. 45 Corn stover has negligible lipid content. This is possibly the reason for the low H 2 concentrations observed in this study.…”
Section: Gas Productionmentioning
confidence: 99%